MdMYB46 could enhance salt and osmotic stress tolerance in apple by directly activating stress‐responsive signals. Issue 12 (26th May 2019) - Chen, Keqin; Song, Mengru; Guo, Yunna; Liu, Lifu; Xue, Hao; Dai, Hongyan; Zhang, Zhihong
Summary: To expand the cultivation area of apple ( Malus×domestica Borkh.) and select resistant varieties by genetic engineering, it is necessary to clarify the mechanism of salt and osmotic stress tolerance in apple. The MdMYB46 transcription factor was identified, and the stress treatment test of MdMYB46 ‐overexpressing and MdMYB46 ‐RNAi apple lines indicated that MdMYB46 could enhance the salt and osmotic stress tolerance in apple. In transgenic Arabidopsis and apple, MdMYB46 promoted the biosynthesis of secondary cell wall and deposition of lignin by directly binding to the promoter of lignin biosynthesis‐related genes. To explore whether MdMYB46 could coordinate stress signal transduction pathways to cooperate with the formation of secondary walls to enhance the stress tolerance of plants, MdABRE1A, MdDREB2A and dehydration‐responsive genes MdRD22 and MdRD29A were screened out for their positive correlation with osmotic stress, salt stress and the transcriptional level of MdMYB46 . The further verification test demonstrated that MdMYB46 could activate their transcription by directly binding to the promoters of these genes. The above results indicate that MdMYB46 could enhance the salt and osmotic stress tolerance in apple not only by activating secondary cell wall biosynthesis pathways, but also by directly activating stress‐responsive signals.